Partycypacja społeczna w planowaniu przestrzennym na przykładzie Polski - Kobielska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
Broadening of social participation is one of the key trends in changes in design and implementation of public policies. Hence, the issue of socialization of decision-making processes is strongly emphasized in sustained development, environmental protection policies and spatial planning. In order to achieve a participatory level in spatial decision-making, proper configuration and intensity of system elements are essential. It involves: 1 rules that establish framework for socialized action; 2 social practice, understood as civic activity; 3 openness of the process manager, that is government and public administration. This article attempts to set spatial planning the case of Poland, with its conditioning rules and practices, in the context of the qualitative analysis of participatory democracy.
Keywords: participation; spatial planning; governance